HUBUNGAN KADAR LIPOPROTEIN A DENGAN KOMPLEKSITAS LESI PEMBULUH DARAH KORONER PADA PENDERITA JANTUNG KORONER DI RSUP DR.SARDJITO YOGYAKARTA - , Iin Novita Nurhidayati Mahmuda; , dr. Lucia Kris Dinarti, SpPD, SpJP(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cardiovascular disease is leading cause of death in developed countries. In 2020 there were estimated to be 25 million deaths each year from cardiovascular disease most of them are coronary heart disease. Traditional risk factors such as smoking, hypertension, diabetes, dyslipidemia reported to affect only 50% of the prevalence and degree of coronary heart disease. It pushes a lot of research on non-traditional risk factors one of which lipoprotein (a). Levels of Lp (a) also reflects the degree of severity and is associated with the number of coronary arteries involved. Research also shows that there are variations in the levels of Lp (a) is quite large (19-70%) in seven different ethnic populations. So the results of research conducted in one country can not necessarily be applied in other countries. This is why makes researchers need to find out the role of Lp (a) as a risk factor for coronary heart disease in Indonesia and its relationship with the complexity of coronary artery lesions. The purpose of this study to determine the relationship of Lp (a) level with the complexity of coronary artery lesions. This is a cross-sectional study. Subjects are male and women patients aged between 20 to 60 years who undergo angiografi coroner for theirs STEMI, NSTEMI or NSTEACS which includes unstable angina pectoris, and stable angina pectoris. Correlation between elevated Lp (a) with the complexity of coronary artery lesions will performed by Pearson test. If the distribution is abnormal we used Spearman test.